Enduring Bonds
VI, 213 p. 4 illus.
Keywords: Young children are social beings. They grow and develop in diverse social and environmental contexts that profoundly affect who they are and what they will become. In this, the first volume of Springer’s Educating the Young Child: Advances in Theory and Research, Implications for Practice, a group of distinguished authors examine an array of interpersonal relationships that are formative in shaping childhood: bonds with adult family members, ties with siblings, interaction with peer groups, and connections with caregivers, teachers, administrators, and service providers. The socio-emotional development of young children has been a significant area of study for decades and early childhood is widely recognized not only as the period during which affective development originates but also as the phase in which the future course of life is set into motion. As life’s pace and complexity continues to increase, expectations for children’s abilities to control themselves and interact effectively with diverse individuals and groups continue to grow. This, the first volume in a series of edited books designed to synthesize research, theory, and practice, will focus on key interpersonal relationships affecting the young child. A distinguished group of authors will examine a wide array of relationships that affect the child today and influence the adult tomorrow—important bonds such as those between caregivers and infants; among siblings; between literate adults and the language-learning child; between the homeless and those providing support services, between principals and young students; and between recently immigrated preschoolers, teachers, and families, to name a few.